2002
DOI: 10.1523/jneurosci.22-10-04103.2002
|View full text |Cite
|
Sign up to set email alerts
|

Projection Neurons in Lamina I of Rat Spinal Cord with the Neurokinin 1 Receptor Are Selectively Innervated by Substance P-Containing Afferents and Respond to Noxious Stimulation

Abstract: Lamina I of the spinal cord is densely innervated by nociceptive primary afferents, many of which contain substance P. It contains numerous projection neurons: the majority of these respond to noxious stimuli, however some are activated by cooling. In the rat, approximately 80% of the projection neurons express the neurokinin 1 (NK1) receptor, on which substance P acts, and most cells with this receptor are activated by noxious stimuli. Lamina I neurons can be classified morphologically into pyramidal, multipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
184
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(200 citation statements)
references
References 38 publications
16
184
0
Order By: Relevance
“…In particular, many lamina I neurons with NK1Rs send axons to brain regions involved in pain processing, while receiving synapses from SP-containing primary afferents (Todd et al, 2002). Therefore, synapses between SP-containing primary afferents and NK1R-containing projection neurons appear to be crucial in determining the intensity of pain signals.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many lamina I neurons with NK1Rs send axons to brain regions involved in pain processing, while receiving synapses from SP-containing primary afferents (Todd et al, 2002). Therefore, synapses between SP-containing primary afferents and NK1R-containing projection neurons appear to be crucial in determining the intensity of pain signals.…”
Section: Introductionmentioning
confidence: 99%
“…The present study examined the relationship of VGlut2, VGlut3 transporters and NKI receptors with fos-I nuclei as both glutamate and NKI receptors have been shown to regulate pelvic reflexes [64,69]. Glutamate is the major excitatory neurotransmitter and recent studies have documented the distribution of glutamate transporters in the lumbosacral cord [2,34,38,51,57,63].…”
Section: Discussionmentioning
confidence: 96%
“…However, as shown in figure 3, VGlut 2 and VGlut3 immunostaining was frequently found in close proximity to the fos-I nuclei in the dorsal horn and medial and lateral gray. The presence of overlapping NKI receptors and fos-immunoreactivity in the medial dorsal horn and DGC suggests a functional role of NKI receptors in the regulation of lumbosacral spinal inputs that make collateral projections to deeper layers of the dorsal horn and project to the brain, in addition to regulating nociception [12,61,62,64].…”
Section: Discussionmentioning
confidence: 99%
“…Among these neuromodulators, SP, the role of which is clearly established and well documented, is considered as a key neuropeptide mediating nociceptive message transmission from peripheral afferents to sensory neurons located in the SC dorsal horn (DH) (4)(5)(6). In particular, it has been shown that projection neurons in lamina I of rat DH expressing neurokinin 1 receptors (rNK1s) are selectively innervated by SP-containing afferents and respond to noxious stimulation (7). Direct structural-functional evidence for SP-mediated nociceptive transmission has also been provided in cats by multidisciplinary studies that combined various approaches, including intracellular recording from DH neurons in vivo, characterization of these neurons on the basis of their responses to peripheral noxious stimulation, cellular labeling by horseradish peroxidase, and electron microscopic identification of synaptic contacts (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In particular, it has been shown that projection neurons in lamina I of rat DH expressing neurokinin 1 receptors (rNK1s) are selectively innervated by SP-containing afferents and respond to noxious stimulation (7). Direct structural-functional evidence for SP-mediated nociceptive transmission has also been provided in cats by multidisciplinary studies that combined various approaches, including intracellular recording from DH neurons in vivo, characterization of these neurons on the basis of their responses to peripheral noxious stimulation, cellular labeling by horseradish peroxidase, and electron microscopic identification of synaptic contacts (6)(7)(8)(9). Moreover, intrathecal injection of SP conjugated to the cytotoxin saporin selectively destroyed DH neurons bearing rNK1 and strongly reduced hyperalgesia after capsaicin treatment, indicating that spinal rNK1 neurons are important for the development of hyperalgesia (4,5).…”
mentioning
confidence: 99%